Observational evidence of EPP–NOx interaction with chlorine curbing Antarctic ozone loss - Gordon, Emily M.; Seppälä, Annika; Funke, Bernd; Tamminen, Johanna; Walker, Kaley A. (2020)
We investigate the impact of the so-called energetic particle precipitation (EPP) indirect effect on lower stratospheric ozone, ClO and ClONO 2 in the Antarctic springtime. We use observations from Microwave Limb Sounder (MLS) and Ozone Monitoring Instrument (OMI) on Aura, Atmospheric Chemistry Experiment – Fourier Transform Spectrometer (ACE-FTS) on SciSat, and Michelson Interferometer for Passive Atmospheric Sound (MIPAS) on Envisat, covering the overall period of 2005–2017. Using the Ap index to proxy EPP, we find consistent ozone increases with elevated EPP during years with easterly phase of the quasi biennial oscillation (QBO) in both OMI and MLS observations. While these increases are opposite to what has been previously reported at higher altitudes, the pattern in the MLS O 3 follows the typical descent patterns of EPP–NO x . The ozone enhancements are also present in the OMI total O 3 column observations. Analogous to the descent patterns found in O 3 , we also found consistent decreases in springtime MLS ClO following winters of elevated EPP. To verify if this is due to a previously proposed mechanism of conversion of ClO to the reservoir species ClONO 2 in reaction with NO 2 , we used ClONO 2 observations from ACE-FTS and MIPAS. As ClO and NO 2 are both catalysts in ozone destruction, the conversion into ClONO 2 would result in ozone increase. We find a positive correlation between EPP and ClONO 2 in the upper stratosphere in the early spring, and the lower stratosphere in late spring, providing the first observational evidence supporting the previously proposed mechanism relating to EPP–NO x modulating Cl x driven ozone loss. Our findings suggest that EPP has played an important role in modulating ozone depletion in the last 15 years. As chlorine loading in the polar stratosphere continues to decrease in the future, this buffering mechanism will become less effective and catalytic ozone destruction by EPP–NO x will likely become a major contributor to Antarctic ozone loss.